Variation in Current Guidelines for Fluoride Varnish Application for Young Children in Medical Settings in the United States - Goff, Sarah L.; Gahlon, Grace; Geissler, Kimberley H.; Dick, Andrew W.; Kranz, Ashley M. (Frontiers in Public Health, 2022)
Background: The United States Preventive Services Task Force recommends that medical providers apply fluoride varnish (FV) to the teeth of all children under six years of age, but less than 10% of eligible children receive FV as recommended. Prior studies suggest that variation in clinical guidelines is associated with low uptake of other evidence-based health-related interventions, but consistency of national guidelines for the delivery of FV in medical settings is unknown. Methods: Recommendations for application of FV in medical settings for children under six years of age were extracted from current FV guidelines from national organizations and compared. Results: Ten guidelines were identified. Guidelines differed in terms of periodicity recommendations and whether FV was indicated for children with a dental home or level of risk of dental caries. Conclusion: Numerous recommendations about FV delivery in medical settings are available to pediatric medical providers. Further study is warranted to determine whether the variation across current guidelines detected in this study may contribute to low FV application rates in medical settings.